Transition from isotropic to digitated growth modulates network formation in Physarum polycephalum. (22nd November 2016) - Vogel, David; Gautrais, Jacques; Perna, Andrea; Sumpter, David J T; Deneubourg, Jean-Louis; Dussutour, Audrey
Abstract: Some organisms, including fungi, ants, and slime molds, explore their environment and forage by forming interconnected networks. The plasmodium of the slime mold Physarum polycephalum is a large unicellular amoeboid organism that grows a tubular spatial network through which nutrients, body mass, and chemical signals are transported. Individual plasmodia are capable of sophisticated behaviours such as optimizing their network connectivity and dynamics using only decentralized information processing. In this study, we used a population of plasmodia that interconnect through time to analyse the dynamical interactions between growth of individual plasmodia and global network formation. Our results showed how initial conditions, such as the distance between plasmodia, their size, or the presence and quality of food, affect the emerging network connectivity.